Réponses

2013-12-30T20:01:42+01:00
Bonsoir,

On remplace à chaque fois x par sa valeur :
A)
B = x^2-2x+3 = 0^2-2\times 0+3 = 3
B)
B = x^2-2x+3 = 1^2-2\times 1+3 = 1-2+3 = 2
C)
B = x^2-2x+3 = 3^2-2\times 3 +3 = 9-6+3 = 6
D)
B = x^2-2x+3  = \left(-3\right)^2 -2\times \left(-3\right)+3 = 9+6+3 = 18

Si tu as des questions, n'hésite pas! =)
2013-12-30T20:01:46+01:00
B=x²-2x+3
Calculer la valeur de l'expression B pour:
A)x=0
B=0-0+3
=3

B) x=1
B=x²-2x+3
=1-2+3
=2

C)x=3
B=3²-2*3+3
=9-6+3
=6

D)x=-3
B=-3²-2*(-3)+3
=9+6+3
=18